1990
DOI: 10.18474/0749-8004-25.2.230
|View full text |Cite
|
Sign up to set email alerts
|

Deterrency of Mexican Bean Beetle (Coleoptera: Coccinellidae) Feeding by Free Phenolic Acids

Abstract: We investigated the role of simple phenolic acid precursors of isoflavonoid phytoalexins, as free compounds, in food selection by the Mexican bean beetle, Epilachna varivestis Mulsant, a pest of soybean, Glycine max Merrill, and other legumes. An aerosol spray method was developed to apply compounds in a uniform and reproducible manner to leaf surfaces of common bean, Phaseolus vulgaris L., a preferred host. Twenty-three compounds were tested in dual choice preference tests. Included were benzoic acid, cinnami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Also, ferulic acid was shown to be involved in maize resistance to the weevil Sitophilus zeamais (Classen et al, 1990). More than half of the common phenolic acids that were tested reduced feeding of the Mexican bean beetle (Coccinellidae) when sprayed on to leaves of its preferred host, the common bean Phaseolus vulgaris (Fischer et al, 1990). Additionally, high levels of phenolic acid content in the older leaves (0.3-1.0%) of Sorghum bicolor significantly reduced feeding by Locusta migratoria (Woodhead and Cooper-Driver, 1979).…”
Section: Biological Activitymentioning
confidence: 99%
“…Also, ferulic acid was shown to be involved in maize resistance to the weevil Sitophilus zeamais (Classen et al, 1990). More than half of the common phenolic acids that were tested reduced feeding of the Mexican bean beetle (Coccinellidae) when sprayed on to leaves of its preferred host, the common bean Phaseolus vulgaris (Fischer et al, 1990). Additionally, high levels of phenolic acid content in the older leaves (0.3-1.0%) of Sorghum bicolor significantly reduced feeding by Locusta migratoria (Woodhead and Cooper-Driver, 1979).…”
Section: Biological Activitymentioning
confidence: 99%
“…On the basis of these rules we have since searched for further potential candidates to inhibit FGFs, examining different libraries of natural products. We found that gentisic acid (GA; 2,5-dihydroxybenzoic acid), a widespread plant secondary metabolite involved in pest defense and a catabolite of aspirin, is a potential inhibitor of FGF (27)(28)(29)(30)(31)(32). Here we show that GA does indeed define a new chemical group of FGF inhibitors, which includes homogentisic acid (HGA; 2-(2,5-dihydroxyphenyl)acetic acid), the toxic agent in alkaptonuria.…”
mentioning
confidence: 92%